Effect of Adventitious Carbon on Pit Formation of Monolayer MoS2. Issue 37 (2nd August 2020) - Park, Sangwook; Siahrostami, Samira; Park, Joonsuk; Mostaghimi, Amir Hassan Bagherzadeh; Kim, Taeho Roy; Vallez, Lauren; Gill, Thomas Mark; Park, Woosung; Goodson, Kenneth E.; Sinclair, Robert; Zheng, Xiaolin
Abstract: Forming pits on molybdenum disulfide (MoS2 ) monolayers is desirable for (opto)electrical, catalytic, and biological applications. Thermal oxidation is a potentially scalable method to generate pits on monolayer MoS2, and pits are assumed to preferentially form around undercoordinated sites, such as sulfur vacancies. However, studies on thermal oxidation of MoS2 monolayers have not considered the effect of adventitious carbon (C) that is ubiquitous and interacts with oxygen at elevated temperatures. Herein, the effect of adventitious C on the pit formation on MoS2 monolayers during thermal oxidation is studied. The in situ environmental transmission electron microscopy measurements herein show that pit formation is preferentially initiated at the interface between adventitious C nanoparticles and MoS2, rather than only sulfur vacancies. Density functional theory (DFT) calculations reveal that the C/MoS2 interface favors the sequential adsorption of oxygen atoms with facile kinetics. These results illustrate the important role of adventitious C on pit formation on monolayer MoS2 . Abstract : In situ environmental transmission electron microscopy (TEM) measurements show that pit formation by thermal oxidation is preferentially initiated at the interface between adventitious carbon (C) nanoparticles and monolayer molybdenum disulfide (MoS2 ), rather than only sulfur vacancies. Density functional theory (DFT) calculations reveal that the C/MoS2 interface favors the sequential adsorption of oxygen atoms with facile kinetics.